Improving Boston Type 1 Keratoprosthesis Procedure: One-Touch Femtosecond-Assisted Preparation and Centration of Donor Carrier Tissue. Issue 2 (March 2014) - Malandrini, Alex; Balestrazzi, Angelo; Canovetti, Annalisa; Rossi, Francesca; Cortesini, Letizia; Lenzetti, Chiara; Pini, Roberto; Menabuoni, Luca
Purpose: We describe a technique to avoid decentration of the visual axis of the Boston type 1 keratoprosthesis (Kpro), performing 2 concentric trephinations with femtosecond laser. Methods: Two concentric side cuts were performed in a donor cornea using the 150-kHz Intralase™ FS laser. Within the same applanation procedure, an 8.5-mm-diameter anterior side cut was performed, followed by a concentric 3-mm-diameter anterior side cut. Results: The technique was successfully replicated in 7 cases. Conclusions: Femtosecond laser-assisted double trephination results in a correctly prepared donor cornea, and in an inner side precisely matched with the prosthesis. At the end of the surgery, the Kpro was correctly centered.